(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is known that after the Second World War in Uzbekistan, production, transport system and roads were in a somewhat difficult situation. By the 70s and 80s of the 20th century, this system had received significant development. Especially in the Tashkent region, progress in the transport system and its impact on society were much more effective. This article will tell you about the positive changes in the transport system over the years.